Assessment on the Physical, Mechanical Properties and Leaching Behaviour of Fired Clay Brick Incorporated with Steel Mill Sludge - Noor Amira Sarani; Azini Amiza Hashim; Aeslina Abdul Kadir; Nur Fatin Nabila Hissham; Mohd Ikhmal Haqeem Hassan; M. Nabiałek; B. Jeż (Archives of Metallurgy and Materials, 2022)
The disposal of industrial steel mill sludge in landfills has frequently received significant concern as the sludge has a very notable potential to contaminate soil surface and groundwater in the long run. Recently, the incorporation of industrial steel mill sludge into fired clay brick has become one of the promising alternative methods as it could produce a lightweight product while minimizing the environmental impact of the waste used. In this study, fired clay bricks as the most common building material were incorporated with 0%, 5%, 10% and 15% of steel mill sludge and fired at 1050°C (heating rate of 1°C/min). The manufactured bricks were subjected to physical and mechanical properties such as firing shrinkage, dry density, and compressive strength while the Toxicity Characteristic Leaching Procedure (TCLP) was conducted to analyze leaching behavior from the manufactured bricks. The results demonstrated that incorporation up to 15% of steel mill sludge reduces the properties up to 27.3% of firing shrinkage, 8.1% of dry density and 67.3% of compressive strength. The leaching behavior of Zn and Cu from steel mill sludge was reduced up to 100% from 7414 to 9.22 ppm (Zn) and 16436 to 4.654 ppm (Cu) after 15% of sludge incorporation. It was observed that high temperature during the firing process would improve the properties of bricks while immobilizing the heavy metals from the waste. Therefore, recycling steel mill sludge into construction building materials could not only alleviate the disposal problems but also promote alternative new raw materials in building industries.